2017
DOI: 10.1038/s41598-017-02817-7
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical age constraints and extinction mechanisms of the Late Triassic Carnian crisis

Abstract: The geological record contains evidence for numerous pronounced perturbations in the global carbon cycle, some of which are associated with mass extinction. In the Carnian (Late Triassic), evidence from sedimentology and fossil pollen points to a significant change in climate, resulting in biotic turnover, during a time termed the ‘Carnian Pluvial Episode’ (CPE). Evidence from the marine realm suggests a causal relationship between the CPE, a global ‘wet’ period, and the injection of light carbon into the atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 37 publications
9
75
0
Order By: Relevance
“…Distinct large-scale intercalations of coarse siliciclastics that interrupt shallow-water carbonate successions in the northwestern Tethys, as well as repeated shifts in the composition of the microflora, from xerophytic to hygrophytic forms, are recorded in sedimentary successions (Roghi et al, 2010;Mueller et al, 2016a and references therein). This evidence, coupled with recent age models based on cyclostratigraphy of gamma-ray and elemental abundances (Zhang et al, 2015;Miller et al, 2017), which assign to the CPE a duration of approximately 1.2 Myr, show that this event was not characterized by uniform climatic conditions and a more complex series of events occurred over such an extended period of time. Furthermore, Sun et al (2016) reported three NCIE in bulk carbonates of the Carnian sedimentary succession of South China (Guizhou): at the base of the Julian 2, at the Julian Tuvalian boundary, and in the Tuvalian 1.…”
Section: Accepted Manuscript !mentioning
confidence: 65%
See 4 more Smart Citations
“…Distinct large-scale intercalations of coarse siliciclastics that interrupt shallow-water carbonate successions in the northwestern Tethys, as well as repeated shifts in the composition of the microflora, from xerophytic to hygrophytic forms, are recorded in sedimentary successions (Roghi et al, 2010;Mueller et al, 2016a and references therein). This evidence, coupled with recent age models based on cyclostratigraphy of gamma-ray and elemental abundances (Zhang et al, 2015;Miller et al, 2017), which assign to the CPE a duration of approximately 1.2 Myr, show that this event was not characterized by uniform climatic conditions and a more complex series of events occurred over such an extended period of time. Furthermore, Sun et al (2016) reported three NCIE in bulk carbonates of the Carnian sedimentary succession of South China (Guizhou): at the base of the Julian 2, at the Julian Tuvalian boundary, and in the Tuvalian 1.…”
Section: Accepted Manuscript !mentioning
confidence: 65%
“…Dal Corso et al A C C E P T E D M A N U S C R I P T ! Miller et al, 2017). Such a pattern suggests that for the NCIE-1 the differences could be linked to local changes in the source of the organic carbon, i.e.…”
Section: Discrepancies In the Magnitudes Of The Negative 13 C Toc Excmentioning
confidence: 94%
See 3 more Smart Citations